Current states in an SNS junction for arbitrary thickness of the normal layer at temperatures close to critical - Sakhnyuk, V.E.; Svidzinsky, A.V. (Condensed Matter Physics, 2003)
The behavior of the order parameter close to the superconductor-normal metal interface is researched. The thickness d of the normal layer is arbitrary and the temperature is close to critical. The method of quasiorthogonality to asymptotics is used to obtain boundary conditions. The expression that describes the dependence of the current states on the normal layer’s thickness is obtained. Asymptotic forms of solution at large and at small d (relatively to the coherence length) are considered.